Measurement of the anomalous like-sign dimuon charge asymmetry with 9 fb(-1) of p(p)over-bar collisions - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Sajot, G.; et al. (Amer Physical Soc, 2011)
We present an updated measurement of the anomalous like-sign dimuon charge asymmetry A(sl)(b) for semileptonic b-hadron decays in 9.0 fb(-1) of p (p) over bar collisions recorded with the D0 detector at a center-of-mass energy of root s = 1.96 TeV at the Fermilab Tevatron collider. We obtain A(sl)(b) = (-0.787 +/- 0.172(stat) +/- 0.093(syst)%. This result differs by 3.9 standard deviations from the prediction of the standard model and provides evidence for anomalously large CP violation in semileptonic neutral B decay. The dependence of the asymmetry on the muon impact parameter is consistent with the hypothesis that it originates from semileptonic b-hadron decays.